1992
DOI: 10.1210/en.131.2.815
|View full text |Cite
|
Sign up to set email alerts
|

Specific antibody to the thyrotropin receptor identifies multiple receptor forms in membranes of cells transfected with wild-type receptor complementary deoxyribonucleic acid: characterization of their relevance to receptor synthesis, processing, structure, and function

Abstract: An antibody to a peptide of the TSH receptor, residues 352-366 which are not present in gonadotropin receptors, specifically identifies three major forms of the receptor on Western blots of detergent-solubilized membrane preparations from Cos-7 cells transfected with full-length rat and human TSH receptor cDNA: 230, 180, and 95-100 kilodaltons (kDa), based on simultaneously run protein standards. The 95- to 100-kDa protein is absent in cells transfected with a mutant receptor with no signal peptide and is sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Such a size is difficult to reconcile with the molecular mass (84.5 kDa) of the amino acid backbone. A monomer of 95-100kDa has been observed in transfected Cos-7 [38] and CHO cells [39]. The accumulation in transfected cells of the mannose-rich monomeric precursor may explain some of these observations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Such a size is difficult to reconcile with the molecular mass (84.5 kDa) of the amino acid backbone. A monomer of 95-100kDa has been observed in transfected Cos-7 [38] and CHO cells [39]. The accumulation in transfected cells of the mannose-rich monomeric precursor may explain some of these observations.…”
Section: Discussionmentioning
confidence: 92%
“…Precursors of the TSH receptor of 230 and 180 kDa have been described in transfected Cos-7 and FRTL-5 cells [38]. Such a size is difficult to reconcile with the molecular mass (84.5 kDa) of the amino acid backbone.…”
Section: Discussionmentioning
confidence: 99%
“…An essential function can be concluded in the case of the rat thyrotropin receptor, where deletion of a sequence containing the putative signal peptide led to nonfunctional receptors (8,9). However, this may not always be the case: for unrelated membrane proteins such as the human sodium calcium exchanger (10) and the human UDP-glucuronosyltransferase 1A6 (11), it was shown that mutants lacking the signal peptide are processed correctly.…”
mentioning
confidence: 99%
“…Deleting the signal peptide sequence of the thyrotropin receptor abolished functionality [172,173]. However, the corticotropin-releasing factor receptor type 2a signal peptide although present, was found to be incapable of mediating ER targeting [174,175].…”
Section: The Glp-1r N-terminal Domain and Its Signal Peptidementioning
confidence: 97%